A framework for management of digital records on the cloud in the public sector of South Africa. Issue 2 (17th June 2021) - Shibambu, Amos; Marutha, Ngoako Solomon
Abstract : Purpose: The purpose of this paper is to investigate a framework for management of digital records on the cloud in South Africa. Design/methodology/approach: This qualitative case study used semi-structured interviews and document analysis to collect data from regulatory documents, records practitioners and chief information officers in the national government departments in South Africa. Findings: This study reveals that despite the advent of cloud computing, government is still struggling with manual paper-based records challenges, as they have not developed a government-owned cloud in which to manage and dispose records. Practical implications: Technological advancements have brought about dramatic changes to the management and disposition of records since cloud computing emerged. The traction gained by cloud computing influences how records are managed and disposed in the cloud storage. Currently, the South African Government manages and disposes records in the government premises as stipulated by the National Archives and Records Service of South Africa Act (1996). This is enforced by the National Archives and Records Service of South Africa, which is the government records regulator because records are on paper-based, microfilms and audio-visual formats. It is hoped that the recommendations and framework proposed in this study may assist the government and related sectors in the adoption and implementation of the cloud computing system for records management and disposal. This may assist in resolving challenges such as missing files, damaged records and archives and long turnaround time for retrieval of records. Social implications: In South Africa, the digital records are securely stored in storage mediums such as hard drives and USBs, to mention but a few. In addition to digital obsolescence faced by the storage mediums, global access to information is hindered because information is limited to those who can visit the archival holdings. The alternative option is to manage and dispose of records in the cloud. The framework and recommendations in this study may also assist in improving information, archives and records management policies and service delivery to the community at large. The framework proposed may be applied as a theory for framing future studies in the same area of cloud computing and used as a resource to guide other future studies and policymakers. Originality/value: This study provides a framework for management of digital records on the cloud in South Africa. It also proposes the promulgation of the Cloud Act to promote unlimited access to state heritage, regardless of time and location. This study is framed on the Digital Curation Centre Life Cycle Model.